Lesão decorrente do posicionamento cirúrgico na pessoa idosa: estudo fundamentado na teoria de Carol Miller - Nova, Felícia Augusta de Lima Vila (2023)
Introduction: Injuries resulting from surgical positioning represent a health problem that affects elderly people and negatively impacts their quality of life. In this context, Carol Miller’s Theory of Functional Consequences emphasizes the assessment of changes related to aging and risk factors as initial actions for the implementation of health interventions aimed at the well-being of older people. Objective: To analyze the occurrence of injury resulting from surgical positioning in elderly patients in the light of Carol Miller's Theory. Method: This is an observational, longitudinal, prospective study with a quantitative approach carried out with 121 elderly people. The research was carried out in the Surgical Block and in the Surgical Clinic of the Lauro Wanderley University Hospital from February to September 2022. Descriptive and inferential statistics were performed for the analysis of quantitative data. The recommendations that regulate studies with human beings were respected; the research was approved by the Research Ethics Committee with opinion number 5,308,368. Results: There was a prevalence of elderly people aged between 60 and 69 years, female, married, with one to four years of schooling and brown skin color; eutrophic nutritional status, with the presence of comorbidities, the most frequent being hypertension. As for the classification of the elderly patients in the preoperative period according to the surgical risk according to the American Society of Anesthesiology, 68.59% were categorized as suffering from systemic disease. Decreased skin turgor was the main age-related change involved with the chances of injury arising from surgical positioning. Regarding the negative functional consequences, 24.79% of the elderly had severe pain and 39.6% had pressure injuries due to surgical positioning. The odds ratio for injury due to positioning was higher among those who had limited mobility and activities, advanced age and who were exposed to ultraviolet rays. In the univariate logistic regression, older people with white skin, with reduced skin turgor and incontinence were more likely to develop positioning injuries. There was a significant statistical correlation between the occurrence of injury due to surgical positioning and the following risk factors: age, skin color, nutritional classification, exposure and sensitivity to ultraviolet rays, incontinence and mobility and limited activities, type of procedure, position adopted on the operating table, support surface, and presence of diabetes mellitus as comorbidity. Conclusion: The research findings are useful because they represent relevant data for reflections on the factors that reinforce the negative functional consequences in the elderly indicated in Carol Miller’s theory, pressure injury and pain resulting from surgical positioning. In this sense, the relevance of the results of this study for Nursing is highlighted in the perspective of guiding care and planning actions, which are aimed at protecting the skin of the elderly who, submitted to surgical intervention, become fragile to risks. It is suggested that nurses reflect on Carol Miller's theoretical assumptions when providing care for elderly patients and carry out new studies with different methodologies for planning interventions so as to prevent pressure injuries resulting from surgical positioning in this type of client.